The purpose of this study was to DEVELOPING SPEAKING LEARNING MATERIAL FOR SOCIAL EXPRESSIONS USING CONTEXTUAL LEARNING AND CARTOON MOVIES (Inqury Narrative Research at Seventh Grade Students of MTs Darussalam Kota Bengkulu): DEVELOPING SPEAKING LEARNING MATERIAL FOR SOCIAL EXPRESSIONS USING CONTEXTUAL LEARNING AND CARTOON MOVIES (Inqury Narrative Research at Seventh Grade Students of MTs Darussalam Kota Bengkulu) - Leni Marlina, Sri Widyaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Developing